On the parameter selection of randomness test - FAN Li-min1; FENG Deng-guo1; CHEN Hua1 (Tongxin xuebao)
The conditions that two different parameters in a same randomness test should satisfy if they are independ- ent with each other was studied based on statistical theory. And a hypothesis method was proposed to test whether two parameters were independent or not. A series of experiments were designed to study the relations among the parameters gather of poker test,which was selected as a research instance by means of this method, and the experiment results were analyzed in details. The method is general and it can be used to deal with other randomness test, such as entropy test and binary derivation test. The work is helpful to select reasonable and scientific parameters in practical randomness test.